A Low Albumin-to-Globulin Ratio Predicts a Poor Prognosis in Patients With Metastatic Non-small-cell Lung Cancer - Lu, Ping; Ma, Yifei; Wei, Shaozhong; Liang, Xinjun (Frontiers in Medicine, 2021)
Objective: The serum albumin-to-globulin ratio (AGR) may be a useful prognostic factor for various cancers. This study aimed to evaluate the prognostic value of the AGR in patients with metastatic non-small-cell lung cancer (NSCLC). Methods: A retrospective study was conducted on patients with stage IV NSCLC diagnosed in Hubei Cancer Hospital from July 2012 to December 2013. The formula for calculating the AGR was serum albumin/total protein-serum albumin. The chi-square test or Fisher's exact test was used to analyze the classified variables. The Kaplan-Meier method was used to analyze the overall survival (OS) rate, which was plotted with the R language. The impact of the AGR on OS and progression-free survival (PFS) was analyzed by a multivariate Cox proportional hazard model. Results: A total of 308 patients were included in the study population. The optimal cutoff values for the AGR in terms of OS and PFS were 1.12 and 1.09, respectively, as determined by X-Tile software. Kaplan-Meier curve analysis showed that the difference in survival rate between patients with different AGR levels was statistically significant (p = 0.04). The OS of patients with a high AGR (≥1.12) was longer than that of patients with a low AGR (<1.12). PFS in the high AGR group were better than those in the low AGR group (16.90 vs. 32.07months, p = 0.008). The univariate and multivariate models proved that the AGR was an independent prognostic factor in metastatic NSCLC patients in terms of both OS (p = 0.009, hazard ratio [HR] = 0.55, 95% confidence interval [95% CI] = 0.35–0.86) and PFS (p = 0.004, HR = 0.55, 95% CI = 0.37–0.83). Conclusion: The AGR, which is measured in routine clinical practice, is an independent prognostic factor in terms of OS and PFS in metastatic NSCLC and can serve as a prognostic tool for metastatic NSCLC.